A semiparametric early warning model of financial stress events - Ian Christensen; Fuchun Li (Bank of Canada, 2013)
The authors use the Financial Stress Index created by the International Monetary Fund to predict the likelihood of financial stress events for five developed countries: Canada, France, Germany, the United Kingdom and the United States. They use a semiparametric panel data model with nonparametric specification of the link functions and linear index function. The empirical results show that the semiparametric early warning model captures some well-known financial stress events. For Canada, Germany, the United Kingdom and the United States, the semiparametric model can provide much better outof- sample predicted probabilities than the logit model for the time period from 2007Q2 to 2010Q2, while for France, the logit model provides better performance for non-financial stress events than the semiparametric model.
Keywords: G01; G17; C12; C14; 330; Financial stability; Econometric and statistical methods